Iron deficiency and iron treatment in the fetal developing brain - a pilot study introducing an experimental rat model - Torben Moos; Tina Skjørringe; Lars Lykke Thomsen (BMC, 2018)
Abstract Background Iron deficiency is especially common in women during the reproductive age and it is estimated that 52% of pregnant women have iron deficiency anemia. Maternal iron deficiency with or without anemia in pregnancy may have consequences for the fetus, where it may have an impact on the cerebral development of the brain. Both animals and adult human studies support that iron deficiency affects psychomotor development, behavioral traits, and cognitive functions in the offspring. However, it has not yet been established whether the availability of sufficient iron is particularly important in certain phases during brain development, and whether possible damages are reversible if iron supplementation is provided during pregnancy. Here we report results from a pilot study in an experimental rat model suitable for introducing iron deficiency in the fetal rat brain. Methods The model was utilized for examination of the potential to reverse changes in fetal brain iron by maternal parenteral iron administration. Fertilized females subjected to iron deficiency without anemia were subcutaneously injected with iron isomaltoside at the day of mating (E0), 14 days into pregnancy (E14), or at the day of birth (Postnatal (P) 0). Blood, brain and liver in the offspring were examined on P0 or in adulthood on postnatal day P70. Results Maternal iron restriction during pregnancy led to significantly lower levels of iron in the brains of newborn rats compared to levels in pups of iron sufficient mothers. Females fed ID diet (5.2 mg/kg Fe) had offspring with significantly lower cerebral iron compared to a control group fed a standard diet (158 mg/kg Fe). Injection of IIM to pregnant ID females on E0 or E14 yielded normalization of Fe in the developing brain known to express elevated levels of capillary transferrin receptors, indicating that the administered iron passed the placenta and fetal blood brain barrier. Conclusions In future studies, this translational model may be applied to examine morphological and biochemical consequences of iron deficiency and iron deficiency treatment in the developing fetal brain.